Improving Students’ Professionalism in Arranging and Developing RPP through Curriculum Development and Learning Planning Courses - Hanifah, Umi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
The aim of this study was to find out the improvement in the ability of PBA students in arranging and developing RPP and their problems through Curriculum and Learning Planning Development courses in PBA Program Study of Sunan Ampel Surabaya University. The results showed that the lectures with portfolio-based learning models could improve the professionalism of PBA students in arranging and developing RPP. The increase was indicated by the results of the RPP assessment conducted by comparing the increase in scores between before and after the RPP was presented, criticized and assessed using the RPP assessment instrument. Before being presented and corrected the result (33.3%) and after the results became (73.3%). The level of problems in compiling and developing RPP is low.Then for the maximal result, it hopes that the portfolio learning model should be variated with the study lesson model in each meeting, especially in arranging lesson plan.